ANALISIS PELUANG PENGHEMATAN KONSUMSI ENERGI LISTRIK DI GEDUNG FAKULTAS SAINS DAN TEKNOLOGI ULB - Pinayungan, Doni; Suwarno, Suwarno; Zambak, M. Fitra (SIGMA TEKNIKA, 2025)
Energy is the stored capacity to perform work. Energy management is a systematic approach to using energy efficiently without reducing the primary function of a building. This study aims to calculate the Energy Use Intensity (EUI), detail energy consumption, and identify potential energy-saving opportunities in the Faculty of Science and Technology building at Labuhanbatu University. Through preliminary and detailed energy audits, EUI values were obtained using three approaches: 41.74 kWh/m²/year (operational time), 77.74 kWh/m²/year (daily usage) — both categorized as efficient, 6.44 (AC room, highly efficient), and 26.18 (non-AC room, very inefficient). Energy-saving opportunities include replacing fluorescent lights with LED lamps, utilizing natural lighting through windows or glass blocks, and reducing water pump usage by installing storage tanks.